2006
DOI: 10.1038/sj.eye.6702480
|View full text |Cite
|
Sign up to set email alerts
|

Pterygium treatment using 5-FU as adjuvant treatment compared to conjunctiva autograft

Abstract: Background The use of conjunctiva autograft, adjunct antimetabolite therapy has been shown to be effective in preventing pterygium recurrence. Objective To compare 5 fluorouracil (5-FU) to conjunctival autograft in the treatment of large, fleshy pterygium. Methods A randomised controlled prospective study of outcome of pterygium treatment using 5-FU as adjuvant treatment compared to conjunctiva autograft. Thirty-five eyes with large pterygium treated with bare sclera conjunctival excision plus 5-FU were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
17
1
1
Order By: Relevance
“…24 Although intra-and post-operative use of 5FU has been discussed previously in isolated reports, few studies have attempted to show the beneficial use of intralesional 5FU injections for early recurrences. 10,11,25 As demonstrated in this study, avoidance of repeat surgery by means of 5FU injection confers the advantages of less scarring, reduced risk of intraoperative and post-operative complications, and all difficulties associated with harvesting more tissue from limited donor sites. Furthermore, the risk of recurrence increases with increasing number of operations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…24 Although intra-and post-operative use of 5FU has been discussed previously in isolated reports, few studies have attempted to show the beneficial use of intralesional 5FU injections for early recurrences. 10,11,25 As demonstrated in this study, avoidance of repeat surgery by means of 5FU injection confers the advantages of less scarring, reduced risk of intraoperative and post-operative complications, and all difficulties associated with harvesting more tissue from limited donor sites. Furthermore, the risk of recurrence increases with increasing number of operations.…”
Section: Discussionmentioning
confidence: 98%
“…In one study in which 5FU was applied to bare sclera, the risk of formation of scleral granuloma was noted to be high. 25 A study that compared the histotoxic effect of MMC with that of 5FU found the latter to be safer in rabbit eyes. 28 In glaucoma filtering surgery, 5FU application is always associated with the conjunctival cover of the area treated or injected subconjunctivally.…”
Section: Discussionmentioning
confidence: 99%
“…This study also re-emphasized that combination of adjunct therapy is better than single adjunct therapy in reducing the rate of recurrence of pterygium. An earlier study by Bekibele et al 25 reported a success rate of bare sclera technique with intraoperative 5-FU group as 88.6% and conjunctival autograft group as 87.9%, respectively. A latter study which compared 5-FU with Mitomycin C as adjunct to conjunctival autograft also by Bekibele et al 27 reported recurrence rates of 8.7 and 11.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The full procedure for selection and recruitment of patients for the study has been described elsewhere 25 but in brief, all patients seen with pterygium encroaching 2 mm or more into cornea (from the limbus) were selected and randomized into one of the two groups. Pterygia of size o2 mm into cornea as well as recurrent pterygium from previous surgery were excluded.…”
Section: Selection Of Patients (Inclusion/exclusion Criteria)mentioning
confidence: 99%
“…, doxorubicin 40 and 5 fluorouracil (5FU) 41 have also been used as adjuvants to prevent recurrences and have shown promising results in some studies.…”
mentioning
confidence: 99%